Archetypes and Responsive Smiles: Classical Statues and American Artists in Rome - Andrea Mariani (European Journal of American Studies)
The essay analyzes the ambivalent response of some major Anglo-American artists and writers to the Roman cultural context, focusing, in particular, on their reaction to classical and neoclassical sculpture. In the 18th and 19th centuries, Rome was often interpreted as “the city of statues,” an image that was shared by visual artists (B. West, W. Allston, H. Greenough, T. Crawford, W. W. Story, H. G. Hosmer) and novelists like Melville, Hawthorne, and James. The function of the archaeological background and the fruitful permanence of dense images from the past are investigated in some of their texts, in terms of an updated archetypal criticism.